Anonymous survey system based on NIZK - Lu LIU; Yu-xi LI; Fu-cai ZHOU (网络与信息安全学报)
Aiming at the security problem that the existing in electronic surveys,such as information fraud,privacy security etc.An anonymous electronic survey scheme based on non-interactive zero knowledge proofs (NIZK) was constructed,which had the characteristics of self-organization,non-interactive,anti-replay,and high efficiency.The system uses the NIZK protocol and the Boneh-Boyen signature scheme to verify the user's identity in non-interactive manner,which guarantees the authenticity of the scheme.The system also uses the Pedersen commitment scheme and the pseudo random function to hide the user's identity and the related information,which guarantees the ano-nymity.Security analysis show that the system has security features such as malicious users attack resistance and anonymity.Finally,the function of the system was also verified and the result show that the system can accomplish all the functions correctly and guarantee the anonymity and authenticity of the system effectively.